Here on the Way to There: A Catholic Perspective on Dying and What Follows - Sillito, John R. (Cistercian studies quarterly, 2006)
The article reviews the book "Here on the Way to There: A Catholic Perspective on Dying and What Follows," by William H. Shannon.